The Effect of Carbon Nanotubes on the Marshall Characteristics of AC-WC Asphalt Mixture - Akbar, Said Jalalul; Maizuar, Maizuar; Muthmainnah, Muthmainnah; Ersa, Nanda Savira; Desmi, Adzuha; Arfiandi, Joni; Adha, Ridwan; Larasati Putri, Ditya (International Journal of Engineering, Science and Information Technology, 2025)
Carbon Nanotubes (CNTs) are cylindrical nanostructures with exceptional mechanical strength, high electrical conductivity, and excellent heat transfer capabilities, making them a promising additive in asphalt mixtures. This study investigates the effect of CNTs on the Marshall parameters of Asphalt Concrete-Wearing Course (AC-WC) mixtures using 60/70 penetration asphalt. CNTs were added to asphalt at 60°C, followed by coarse and fine aggregates preheated to 150°C. Marshall parameter tests were conducted on the samples, and the results showed a significant increase in stability compared to conventional asphalt. Asphalt stability increased by 9%, with the highest value obtained at a CNT concentration of 0.015%, reaching 2177.83 kg. The optimal stability was achieved at a CNT concentration of 0.015%. This study demonstrates that CNTs can be effectively utilized to enhance the performance of AC-WC asphalt mixtures. The flow values decreased as the CNT content increased because CNTs make the asphalt mixture stiffer, improving temperature resistance.